Hypnic headache - a rare primary headache disorder with very good response to indomethacin - Dolezil, David; Mavrokordatos, Charis (Neuro-endocrinology letters, 2012)
Hypnic headache (HH) is considered as a disorder of the circadian rhythm, mostly affecting the elderly and generally considered a benign disorder, but the pathophysiology of hypnic hedache remains unclear. Various treatments have been suggested for hypnic headache, especially lithium and indomethacin. We report the case of HH fulfilling The International Classification Headache Disorders, 2nd edition criteria (ICHD-II). A 64-year-old woman, who suffered from dull headaches strictly during the night for a period of 5 months. Attacks of headache lasted from 30 to 150 minutes, with a frequency usually 4 times per week. The patient was started on indomethacin 50 mg twice a day (BID). From day 25 on she was free of hypnic headache. On day 31 we tapered the daily dose of indomethacin to 50mg at bedtime, the patient was still without headache. On day 60 the treatment was stopped. 30 months after day 60, the patient was still headache free. We reported the first Czech patient with HH with very good therapeutic response to indomethacin. The effect of therapy with indomethacin 50mg BID was very fast and stable.
Keywords: ženské pohlaví; Female; Headache Disorders, Primary; lidé středního věku; Anti-Inflammatory Agents, Non-Steroidal; Humans; lidé; Indomethacin; Middle Aged; indukce remise; primární bolesti hlavy; antiflogistika nesteroidní; Remission Induction; indomethacin; výsledek terapie; Treatment Outcome